Model Keberlanjutan Usahatani Padi Sawah Tadah Hujan Untuk Mendukung Peningkatan Kesejahteraan Petani dan Ketahanan Pangan - Rasidin, Rasidin; Sumartan, Sumartan; Nirmasari, Dian; Adelia, Dian; Dahar, Darmiati (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
The conversion of rainfed rice fields into housing and development projects threaten the sustainability of agriculture, farmers' welfare, and food security in Sidenreng Rappang Regency. This study aims to analyze the level of sustainability and identify sensitive attributes that affect rainfed rice farming in Pitu Riawa District in response to the pressure of land use change. The research method uses the Multi-Dimensional Scaling (MDS) approach which uses Rapfish Software to analyze sustainability indices based on five dimensions, namely ecology, economy, social, legal and institutional, and technology. Data were collected through observations, in-depth interviews with 33 farmers, and Focus Group Discussions (FGD) with stakeholders. The results of the analysis showed that the sustainability status of rainfed rice farming in Pitu Riawa District was in the "quite sustainable" category with an overall index of 58,46. Further leverage analysis revealed key sensitive attributes in each dimension, namely the reduction of water catchment areas (ecological dimension), the decline in farmers' income (economic dimension), changes in the social structure of the community (social dimension), the importance of extension to farmers (legal and institutional dimension), and the technological adaptation of the non-agricultural sector (technological dimension). These findings recommend the need for policies and interventions focused on these sensitive attributes to improve the sustainability of rainfed rice farming.